Christy : a new beginning - Gabler, Deboragh; Lilly, Brenda; McBrearty, Don.; Smith, Lauren Lee, 1980-; Ladd, Diane; Finlay-McLennan, Stewart; Waterston, James, 1969-; George, Laszlo; Mattiussi, Roger; Ramin, Ron.; Healey, Kate.; Schmidt, Philip; et al. ([United States?] : Trimark Home Video, c2000., 2001)
As she prepares for her wedding, Christy receives an unexpected visitor. When a sudden storm hits, Christy becomes stranded in a nearby cabin and becomes sick with a high fever. As the storm passes and she recovers, the right decisions become clear.
Based on the novel and characters by Catherine Marshall.
Director of photography, Laszlo George ; editor, Roger Mattiussi ; music, Ron Ramin ; costume designer, Kate Healey ; production designer, Phil Schmidt.
Lauren Lee Smith, Diane Ladd, Stewart Finlay-McLennan, James Waterson.
MPAA rating: PG.
DVD.
Closed-captioned.
Keywords: Christian life -- Drama; Mountain life -- Drama; Man-woman relationships -- Drama; Feature films; Television adaptations; Television mini-series.; Films for the hearing impaired